Environmental Metagenomic Assemblies Reveal Seven New Highly Divergent Chlamydial Lineages and Hallmarks of a Conserved Intracellular Lifestyle - Pillonel, Trestan; Bertelli, Claire; Greub, Gilbert (Frontiers in Microbiology, 2018)
The Chlamydiae phylum exclusively encompasses bacteria sharing a similar obligate intracellular life cycle. Existing 16S rDNA data support a high diversity within the phylum, however genomic data remain scarce owing to the difficulty in isolating strains using culture systems with eukaryotic cells. Yet, Chlamydiae genome data extracted from large scale metagenomic studies might help fill this gap. This work compares 33 cultured and 27 environmental, uncultured chlamydial genomes, in order to clarify the phylogenetic relatedness of the new chlamydial clades and to investigate the genetic diversity of the Chlamydiae phylum. The analysis of published chlamydial genomes from metagenomics bins and single cell sequencing allowed the identification of seven new deeply branching chlamydial clades sharing genetic hallmarks of parasitic Chlamydiae. Comparative genomics suggests important biological differences between those clades, including loss of many proteins involved in cell division in the genus Similichlamydia, and loss of respiratory chain and tricarboxylic acid cycle in several species. Comparative analyses of chlamydial genomes with two with two proteobacterial orders, the Rhizobiales and the Rickettsiales showed that genomes of different Rhizobiales families are much more similar than genomes of different Rickettsiales families. On the other hand, the chlamydial 16S rRNA exhibit a higher sequence conservation than their Rickettsiales counterparts, while chlamydial proteins exhibit increased sequence divergence. Studying the diversity and genome plasticity of the entire Chlamydiae phylum is of major interest to better understand the emergence and evolution of this ubiquitous and ancient clade of obligate intracellular bacteria.